Interactions among heavy metal bioaccessibility, soil properties and microbial community in phyto-remediated soils nearby an abandoned realgar mine. (January 2022) - Xiao, Weiwei; Lin, Guobing; He, Xiaoman; Yang, Zhaoguang; Wang, Lin
Abstract: Soil samples were collected from a representative arsenic (As) contaminated region under phytoremediation of hyperaccumulation plants. Relative abundance and diversity of microbial communities in the soil samples were characterized via 16S rRNA genes sequencing. At the phylum level, Proteobacteria, Actinobacteria, Acidobacteria, Bacteroidetes, Gemmatimonadetes and Firmicutes shows the highest abundance, accounting for more than 90 % of the classified sequences in the soil samples. Physicochemical parameters including pH, total organic carbon (TOC), cation exchange capacity (CEC), and electrical conductivity (EC), and heavy metal concentrations including total and bioaccessible contents in the soil samples were determined to investigate potential relationships between the microbial communities and the environmental factors. Principal component analysis (PCA) based on the operational taxonomic units (OTUs) matrix revealed distinct separation among the samples. The soil pH was confirmed as the dominant force to discriminate the soil samples with similar land use type and heavy metal contamination. There was little relevance between the total concentrations of heavy metals and the microbial communities. However, the bioaccessible concentrations of heavy metals were associated with the physicochemical parameters and relative abundances of bacterial genera according to correlation analyses. Although the soil samples were considerably contaminated by As, the abundances of bacterial phyla linked with As were lower than 1.0 % in most of the soil samples. The results indicated that the abundances of microbial communities in the soils were the consequence of concerted effects from all the environmental factors. Graphical abstract: Image 1 Highlights: Bioaccessible heavy metals were related to the physicochemical parameters. The soil pH was the dominant force to discriminate the microbial communities. Lack of correlation was found between total heavy metals and microbial communities. Lower than 1.0 % of the bacterial phyla were linked with arsenic in the soil samples.